HUBUNGAN PEMAHAMAN INKUIRI ILMIAH DENGAN KEMAMPUAN KOGNITIF SISWA SMA PADA MATERI EKOSISTEM - Ghina Mutiara Abas, - (2019)
This research is aimed to obtain information and analyze the relationship between understandings about scientific inquiry and students' cognitive ability in senior high school students. The participants are 91 students in one of senior high school in Bandung, they were 29 students from tenth grade,28 students from elevent grade and 34 students from twelfth grade . The understandings about scientific inquiry data were gained using VASI (Views About Scientific Inquiry) questionnaire, and students' cognitive ability data were obtained from 30 questions; 27 multiple choices and 3 essays. The result of scientific inquiry comprehension in scientific investigations all begin with a question and do not necessarily test a hypothesis aspect show the highest students' percentage that is categorized as informed. In addition, this aspect shows that the twelfth grade students have the highest percentage with 76.47%, followed by tenth grade students with 58.62%, and lastly eleventh grade students merely have 3.57%. Furthermore, based on the students' cognitive ability test, the tenth grade and twelfth grade students show the similarities in cognitive ability, but different from eleventh grade. The correlation test result shows the direct relationship between understandings about scientific inquiry and students' cognitive ability in concept of ecosystem, but the strength of the relationship is included in the low category. Cognitive ability in concepts of ecosystem contribute 8,41% of the understandings about scientific inquiry. Key word: Scientific Inquiry, Cognitive Ability, Ecosystem